Conditional Knockout of Raptor/mTORC1 Results in Dentin Malformation - Xie, Furong; Dai, Qinggang; Liu, Xiao; Wang, Jun (Frontiers in Physiology, 2019)
mTORC1 signalling plays an important role in extracellular and intracellular signals, including growth factors, nutrients, energy metabolism and stress. However, the functional role of mTORC1 in dentinogenesis is unknown. To study the role of Raptor/mTORC1 in dentinogenesis, an Osx-Cre Raptorfl/fl (Rap-Osx) mouse, in which Raptor was conditionally deleted in odontoblasts and bone-producing mesenchyme, was generated, and postnatal tooth development was compared between Rap-Osx mice and control littermates. Rap-Osx mice presented a phenotype known as dentinogenesis imperfecta and had smaller tooth volume, a thinner dentin layer and a larger pulp chamber. The proliferation and differentiation of odontoblasts/preodontoblasts were attenuated in mutant mice, which was likely responsible for the defects in dentinogenesis. Raptor/mTORC1-pS6K1 signalling was inactivated during tooth development in Rap-Osx mice, whereas it was activated in control mice. These results indicate that Raptor/mTORC1 plays an critical role in dentinogenesis via promoting odontoblast proliferation and differentiation. Raptor/mTORC1 might regulate tooth development through the pS6K1 signalling pathway.